1990
DOI: 10.1016/s0022-5347(17)39620-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of an α1-Blocker, YM617, in the Treatment of Benign Prostatic Hypertrophy

Abstract: A recently synthesized alpha 1-blocker, (R)(-)-5-[2-[[2-(o-ethoxyphenoxy)ethyl]amino]propyl]-2- methoxybenzenesulfonamide hydrochloride (YM617), was evaluated in 270 patients with benign prostatic hypertrophy in a double-blind study. After 2 weeks on placebo the patients were assigned at random to 4 groups: group P--placebo, group L--0.1 mg., group M--0.2 mg. and group H--0.4 mg. of YM617. Comparing the placebo to the treatment period, subjective symptoms, such as nocturia and urgency, were significantly decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
3
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(91 citation statements)
references
References 12 publications
3
84
3
1
Order By: Relevance
“…However, a placebo-controlled double-blind study in Japan showed that a 4-week treatment with terazosin 2 mg daily improved subjective symptoms [23]. Although tamsulosin at 0.2 mg daily failed to improve irritative symptoms in the initial study by Kawabe et al [12], two of three irritative symptoms were improved in the present trial. These differences may be attributable to variation in the questionnaires used in the two studies for evaluating the severity of symptoms.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…However, a placebo-controlled double-blind study in Japan showed that a 4-week treatment with terazosin 2 mg daily improved subjective symptoms [23]. Although tamsulosin at 0.2 mg daily failed to improve irritative symptoms in the initial study by Kawabe et al [12], two of three irritative symptoms were improved in the present trial. These differences may be attributable to variation in the questionnaires used in the two studies for evaluating the severity of symptoms.…”
Section: Discussioncontrasting
confidence: 53%
“…Subsequently, terazosin has been widely used in Japan at doses of 1± 2 mg daily (the recommended dose established for BPH). Tamsulosin is also used in high doses in Western countries (as high as 0.4 mg daily), but a dose of 0.2 mg daily is recommended in Oriental countries [12,14].…”
Section: Discussionmentioning
confidence: 99%
“…The mean (sd) Q max measured before treatment was Six patients had abnormal laboratory test values but these changes were not considered to be related to the similar in both groups ( improved the subjective and objective symptoms of Table 4 The incidence of adverse reactions related to study whereas 18 patients in the terazosin group experienced medication a total of 27 adverse reactions considered to be possibly or probably related to study medication and generally that reported by others [21][22][23][24][25][26]. The safety profile as adverse reactions determined from the incidence of adverse reactions and eÂect on blood pressure and pulse rate was similar to …”
Section: Methodsmentioning
confidence: 93%
“…In studies subjective symptoms as assessed from the IPSS, and objective examinations (e.g. urinary flow rate, PVR, in Japan [21,22], Europe [23][24][25] and the USA [26], tamsulosin, at a dose of 0.2-0.4 mg once daily, produced blood pressure and pulse rate in the supine and standing positions, complete blood cell count, serum biochemistry symptomatic improvement without aÂecting blood pressure and pulse rate in patients with BPH. Further, patients and routine urine analysis) were performed according to the schedule in Table 1.…”
mentioning
confidence: 99%
“…45 In contrast to these agents is tamsulosin, which is highly selective for the a 1A -adrenoreceptor subtype 4,46 and thus has been reported to produce symptomatic improvement of BPH without affecting blood pressure or heart rate and without requiring dose titration (although approximately 20% of patients do require the 0.8-mg dose). 47 Perhaps because of its higher pharmacological selectivity for a 1A -receptors in the bladder neck, seminal vesicles, and vas deferens however, tamsulosin is associated with a significant incidence of ejaculatory dysfunction. It is impossible to know actually if it is abejaculation or retrograde ejaculation.…”
Section: Medical Therapy For Bphmentioning
confidence: 99%